Tipologi Ventilasi Bangunan Vernakular Indonesia - Gun Faisal; Nindyo Suwarno; Dimas Wihardyanto (JURNAL ARSITEKTUR, 2012)
Buildings are the world's largest energy absorbers. They absorb 48 percents of energy, transportation absorbs 21 percent of it, while the rest of the energy is used by other sectors. The use of Air Conditioner that takes up a lot of energy is replaced by natural ventilation to reduce energy consumption. This paper discusses how the ventilation system and the model on the vernacular buildings in Indonesia, and aims to determine and identify the type of ventilation system. Ventilation is one way of vernacular buildings to cope with climate conditions. This study is applies qualitative method. It study is conducted to observe the subject and compare it to related literature and analyze the result based on related theories. This paper explore Â the type of ventilation system in some vernacular buildings in Indonesia. In the end, the author found out that there are four types of ventilaton sytem of vernacular building in Sumatera, Java, Bali, Lombok, Kalimantan, Sulawesi, and Papua.